2014
DOI: 10.1002/jmri.24824
|View full text |Cite
|
Sign up to set email alerts
|

MRS measured fatty acid composition of periprostatic adipose tissue correlates with pathological measures of prostate cancer aggressiveness

Abstract: Fatty acid composition is altered in the PPA tissue of patients with aggressive prostate cancer. Ex vivo MR spectroscopy may be a useful tool in studying the altered fatty acid metabolism in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…One of our hypotheses focused on PPAT due to previous in vitro research that showed that coculture with PPAT produced an aggressive phenotype in prostate cancer cells 28,29 . One study used magnetic resonance spectroscopy and found that the fatty acid composition was altered in PPAT of patients with aggressive prostate cancer 30 . When observing secretions from PPAT explants, PPAT‐conditioned media from more obese patients caused significantly more proliferation of prostate cancer and endothelial cells in vitro than PPAT‐conditioned media obtained from leaner men 31 .…”
Section: Discussionmentioning
confidence: 99%
“…One of our hypotheses focused on PPAT due to previous in vitro research that showed that coculture with PPAT produced an aggressive phenotype in prostate cancer cells 28,29 . One study used magnetic resonance spectroscopy and found that the fatty acid composition was altered in PPAT of patients with aggressive prostate cancer 30 . When observing secretions from PPAT explants, PPAT‐conditioned media from more obese patients caused significantly more proliferation of prostate cancer and endothelial cells in vitro than PPAT‐conditioned media obtained from leaner men 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential for enhanced fatty acid release and transfer to PCa cells, the composition of fatty acids in the PPAT is commonly altered in PCa compared to benign prostatic tissue . For example, Quiroga et al.…”
Section: Potential Mechanistic Links Between Peri‐prostatic Adipose Tmentioning
confidence: 99%
“…Similarly, Iordanescu et al. used magnetic resonance spectroscopy to show that PPAT from patients with more aggressive PCa has a higher ratio of monounsaturated/saturated fatty acids. However, this relationship was not observed with high Gleason scores (7 vs 6), which may be attributable in part to those patients with Gleason score 7 being a mixed population of 4 + 3 (only four patients) and 3 + 4 (13 patients).…”
Section: Potential Mechanistic Links Between Peri‐prostatic Adipose Tmentioning
confidence: 99%
“…Periprostatic adipose tissue (PPAT), a white fat depot surrounding the prostate capsular-like structure, has been recognized to have the potential to exert pro-tumoral endocrine and paracrine influences on prostate cancer cell’s biological phenotypes [ 4 ]. There is now evidence that obesity and overweight result in excess fat deposit at PPAT [ 5 ], altered fatty acid profile [ 6 ], migration of tumor cells [ 7 ], secretion of a variety of adipokines, such as interleukin-1 beta (IL-1b), osteopontin, leptin, tumor necrosis factor alpha (TNF-a), and decreased adiponectin, thus contributing to a tumor microenvironment that ultimately facilitates PCa aggressiveness [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%